Proceedings of the 4th International Conference on Sport Science, Health, and Physical Education (ICSSHPE 2019) 2020
DOI: 10.2991/ahsr.k.200214.082
|View full text |Cite
|
Sign up to set email alerts
|

Long Jump Ability: A Comparison Between Students with High and Low Physical Fitness

Abstract: Long jump ability is a skill that must be possessed by high school students as a part of the achievement of physical education learning outcomes. This study was aimed at determining the differences in long jump learning outcomes in students with high and low fitness levels. This research is an experimental research involving 30 students from Vocational School of Pasundan 1 Cianjur, Indonesia, as the samples. The research instruments used in this study were the Indonesian physical fitness test for high school a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…It is confirmed that a physically trained student can teach effectively different movements that differ from his sports specialization [39]. However, indicate that the level of physical fitness of students should be taken into account [41]. A certain level of understanding and awareness of the program and the planned impact of the program must be achieved before the training can begin.…”
Section: Discussionmentioning
confidence: 91%
“…It is confirmed that a physically trained student can teach effectively different movements that differ from his sports specialization [39]. However, indicate that the level of physical fitness of students should be taken into account [41]. A certain level of understanding and awareness of the program and the planned impact of the program must be achieved before the training can begin.…”
Section: Discussionmentioning
confidence: 91%
“…Dwijayanthi (2011: 105) said that the characteristics of children who have good nutritional status, namely weight growth in accordance with height and not easily tired. Next Kastrena et al, (2020) said that children with good nutritional status have high endurance and have good work power so that children are excited and active in the learning process. However, if the nutritional condition is not good, it will make interest and enthusiasm for learning decrease which certainly affects the learning process.…”
Section: The Influence Of Learning Motivation Nutritional Status and ...mentioning
confidence: 99%
“…Gerak manipulatif merupakan bentuk penguasaan pada sebuah objek atau benda (Purbaya 2023). Pengertian lain terakit gerak manipulatif yaitu bentuk keterampilan untuk memanipulasi objek sambil bergerak (Kastrena et al 2020). Untuk dapat melaksanakan pembelajaran yang efektif terkait peningkatan gerak dasar dan penguatan literasi numerasi maka perlu adanya modifikasi.…”
Section: Kajian Teoriunclassified